2022
DOI: 10.3390/biomedicines10081997
|View full text |Cite
|
Sign up to set email alerts
|

The Ratio of the Size of the Abdominal Aortic Aneurysm to That of the Unchanged Aorta as a Risk Factor for Its Rupture

Abstract: Background: A ruptured abdominal aortic aneurysm is a severe condition associated with high mortality. Currently, the most important criterion used to estimate the risk of its rupture is the size of the aneurysm, but due to patients’ anatomical variability, many aneurysms have a high risk of rupture with a small aneurysm size. We asked ourselves whether individual differences in anatomy could be taken into account when assessing the risk of rupture. Methods: Based on the CT scan image, aneurysm and normal aort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 35 publications
1
1
0
Order By: Relevance
“…This study complements the studies carried out by Jusko et al [ 22 ], Fillinger et al [ 60 ], Di Martino et al [ 61 ], and Kimura et al [ 62 ], who demonstrated that the geometric analysis of the AAA provides valuable information, with a predictive role superior to that of the maximum diameter in the case of the risk of AAA rupture.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…This study complements the studies carried out by Jusko et al [ 22 ], Fillinger et al [ 60 ], Di Martino et al [ 61 ], and Kimura et al [ 62 ], who demonstrated that the geometric analysis of the AAA provides valuable information, with a predictive role superior to that of the maximum diameter in the case of the risk of AAA rupture.…”
Section: Discussionsupporting
confidence: 84%
“…In a recent study, Jusko et al [ 22 ] revealed that the ratio of the maximum aneurysmal diameter to the aorta diameter at the aneurysmal neck is a better imaging marker for AAA rupture than the maximum diameter (as indicated by the area under the curve (AUC) values using ROC analysis, AUC: 0.783 versus 0.650).…”
Section: Introductionmentioning
confidence: 99%